2019
DOI: 10.1111/jbi.13556
|View full text |Cite
|
Sign up to set email alerts
|

Congruent patterns of functional diversity in saproxylic beetles and fungi across European beech forests

Abstract: Aim Beech forests comprise a globally unique temperate forest type in Europe. The dominance of beech in these forests developed during the ongoing post‐glacial northward re‐colonization, concurrently with intensified forest use by humans. We investigated how these two processes together with climate shaped the patterns of functional diversity of two major species groups involved in wood decomposition and whether functional diversity is determined on the local or regional species pool level. Location European b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 67 publications
(108 reference statements)
2
20
0
Order By: Relevance
“…Our finding of site-and region-specific differences in TreM dynamics and composition in both World Heritage areas complements earlier reports of beech forest diversity. Moreover, in the design of measures directed at conserving the overall diversity in beech forests, this study supports a research approach based on regions that differ in their soil, climate, and tree mixtures, rather than on different local stands within a single region [45,59].…”
Section: Implications For Nature Conservation In Broadleaf Forestssupporting
confidence: 62%
See 1 more Smart Citation
“…Our finding of site-and region-specific differences in TreM dynamics and composition in both World Heritage areas complements earlier reports of beech forest diversity. Moreover, in the design of measures directed at conserving the overall diversity in beech forests, this study supports a research approach based on regions that differ in their soil, climate, and tree mixtures, rather than on different local stands within a single region [45,59].…”
Section: Implications For Nature Conservation In Broadleaf Forestssupporting
confidence: 62%
“…Primeval temperate forests serve as an important reference baseline for integrative management strategies [38]. Studies of beech forests have focussed on their stand structure [23,24,29]; the amount and composition of deadwood [39]; and the composition of fungi, bryophytes [40][41][42], and beetles [34,[43][44][45]. By contrast, the composition and dynamics of TreMs in natural forests of European and Oriental beech remain poorly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial distance played a role only for saproxylic beetles and spiders, but not for microbes (fungi and bacteria), and even for both arthropod taxa, space played only a minor role. Fungi and saproxylic beetles are often inter‐related in deadwood ecosystems (Weslien et al 2011, Thorn et al 2015, Jacobsen et al 2018, Hagge et al 2019a, Seibold et al 2019). However, the variation in the beetle assemblages could not be explained by adding fungal composition to the beetle model (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For example, among the determinants of community assembly at larger spatial extents, geographical distance (neutral processes) was shown to be more important than environmental factors (niche process), as demonstrated in pan‐European vs. country‐wide analyses (Keil et al., 2012; Qian et al., 2005). However, recent studies have shown regional effects with an explicit spatial clustering, such as the effects of biogeographical history on local assemblages over a continental spatial extent in Europe (Hagge et al., 2019; Jiménez‐Alfaro et al., 2018). These observations demonstrate the importance of resolving spatial structure into multiple spatial scales in studies on species turnover.…”
Section: Introductionmentioning
confidence: 99%